Reparation of peripheral nerves with fibrin glue prepared from snake venom: preliminary results - Juan, Fabio Cardoso (1995)
A new fibrin glue obtained from snake venom is presented, with possible utilization in various fields of medicine. The preparation procedures and tests in the reparation of peripheral nerves are described. The preliminary results were similar to the conventional fibrin glue procedure.